The Effect of Work Discipline, Physical Work Environment and Employee Professionalism on Employee Performance - Anggraini, Rani; Febrian, Wenny Desty (Green Publisher, 2025)
This study aims to analyze the effect of work discipline, physical work environment, and professionalism on employee performance at SMP N XXX Jakarta. Employee performance is one of the important factors in achieving organizational goals, so it is necessary to identify factors that can affect it. In this study, work discipline, physical work environment, and professionalism were selected as independent variables that are thought to play a significant role in employee performance. The research method used is quantitative with an associative approach. Data were collected through questionnaires distributed to employees of SMPN XXX Jakarta, with a sample of 33 respondents. Data analysis was carried out using multiple linear regression tests to see the partial effect of each independent variable on employee performance. The results showed that work discipline has a significant effect on employee performance, with a calculated t value of 3.505 greater than t table 2.019 and a significant value of 0.02 smaller than 0.05. The physical work environment also has a significant effect on employee performance, with a t value of 6.729 greater than t table 2.019 and a significant value of 0.01 smaller than 0.05. In contrast, professionalism does not have a significant effect on employee performance, with a calculated t value of 1.095 smaller than the t table 2.019 and a significant value of 0.283 greater than 0.05. The conclusion of this study is that work discipline and physical work environment are factors that have a significant effect on employee performance at SMPN XXX Jakarta, while professionalism has no significant effect. Therefore, management needs to focus on increasing work discipline and improving the physical work environment to improve employee performance optimally. This study also provides suggestions for future researchers to explore other variables that may affect employee performance.